2019
DOI: 10.1109/tii.2018.2879907
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Frequency Response From Industrial Heating Loads for Electric Power Systems

Abstract: Increasing penetration of renewable generation results in lower inertia of electric power systems. To maintain the system frequency, system operators have been designing innovative frequency response products. Enhanced Frequency Response (EFR) newly introduced in the UK is an example with higher technical requirements and customized specifications for assets with energy storage capability. In this paper, a method was proposed to estimate the EFR capacity of a population of industrial heating loads, bitumen tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Current DR schemes can be categorized into two types, depending on whether the customers are passively scheduled or if they actively make decisions. In the first type, several DR customers are aggregated, modeled as a virtual power plant (VPP), and dispatched in the unit commitment [23], optimal power flow [24], and frequency regulation [25]. This approach is easily deployed in practice.…”
Section: B Second Contribution and Its Related Workmentioning
confidence: 99%
“…Current DR schemes can be categorized into two types, depending on whether the customers are passively scheduled or if they actively make decisions. In the first type, several DR customers are aggregated, modeled as a virtual power plant (VPP), and dispatched in the unit commitment [23], optimal power flow [24], and frequency regulation [25]. This approach is easily deployed in practice.…”
Section: B Second Contribution and Its Related Workmentioning
confidence: 99%
“…Consequently, it is important to identify industrial/commercial loads based on DR service requirements. The potential use of bitumen tanks, being representative of industrial heating loads, to provide EFR in the GB power system has been investigated, with a high level of satisfaction [19], where the required EFR response was provided by changing the temperature set‐points of the bitumen tanks. It has also been demonstrated that battery energy storage systems can be deployed on industrial manufacturing sites, equipped with combined heat and power units, to unlock their potential to provide a firm frequency response (<10 s) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Small-to-midsize combined heat and power (CHP) units, which are widely used in industries, are well positioned to provide flexibility services, pointed out by the U. S. Department of Energy [6]. A typical flexibility service, namely frequency response [7], [8], is one of the key areas where CHP has been attracting increased attention. A flexible CHP system at Princeton University which was designed to support campus' heat and electricity needs, has been applied to enable frequency response [9].…”
Section: Introductionmentioning
confidence: 99%